(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Cervical cancer is a totally preventable cancer in females. There is continuous effort ongoing to overcome the existing deficiencies in the screening and vaccination programme. The goal is to improve the situation so that maximum reduction in the incidence and mortality of cervical cancer can be achieved. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 94-96